Efficacy of balance training to improve balance of young female gymnasts - Lockard, M.; Gable, T. (Science of Gymnastics Journal, 2023)
Gymnastics is a popular sport that has potential strength, flexibility, and personal growth benefits for athletes. Both static and dynamic balance are developed from a young age and are fundamental to higher-level gymnastics. PURPOSE: To assess the efficacy of a balance training protocol in improving the dynamic balance of young female gymnasts. METHOD: 19 female Junior Olympic (JO) Level 3 gymnasts, ages 6-11, were randomly assigned to the Balance Training (BT) or control groups. The BT group completed a variety of balance exercises during each practice (2x/wk for eight weeks), including one-footed balance, hopping skills, and leaps onto surfaces of varying stability. Gymnasts in the control group continued with their normal gymnastics practices. Gymnasts were tested before training, after week 4, and after week 8 to assess improvements in the Balance Error Scoring System (BESS), Star Excursion Balance Test (SEBT), Center of Pressure Path length (COP Path length), and Joint Position Sense (JPS) scores. RESULTS: An improvement in SEBT for the gymnasts` dominant foot reaching anteriorly (p=0.03) was observed. Otherwise, there were no significant differences between improvements in scores for the control group and the experimental group. CONCLUSION: JO Level 3 gymnasts, who are early in their training and development, demonstrated no additional benefit from twice weekly balance training beyond normally prescribed practice and skills training. While anecdotal evidence suggested a possible acute effect on balance performance immediately following balance exercises, further research is needed.